Balancing Page Endurance Variation Between Layers to Extend 3D NAND Flash Memory Lifetime - Jialin Wang; Yi Fan; Yajuan Du; Siyi Huang; Yu Wan (Micromachines)
With vertical stacking, 3D NAND’s flash memory can achieve continuous capacity growth. However, the endurance variation between the stacked layers becomes more and more significant due to process variation, which will lead to the underutilization of many pages and seriously affect the lifetime of 3D NAND’s flash memory. We investigated the endurance variation characteristics between layers and divided the stacked layers into the top, middle, and bottom layers according to the endurance characteristics. We found that the endurance of the bottom layer pages is much weaker than that of the other two layers, which is the primary factor that affects the lifetime of 3D NAND’s flash memory. In response to this endurance variation feature, we proposed a new layer-aware write strategy, called LA-Write. First of all, the write–skip unit in LA-Write will reduce the wear pressure of the pages through write–skip operations. Secondly, LA-Write maintains a layer-aware table, which stores the probability of pages in different layers performing the write–skip operation. Setting the probability of the bottom pages to the highest value will result in more write–skip operations on the bottom layers, mitigating endurance variations between layers. We carried out our experiments of LA-Write on DiskSim, a popular SSD simulator. Compared to existing schemes, experimental results show that LA-Write can greatly increase SSD’s lifetime.